Ways To Improve the Teaching of Foreign Languages in Technical Universities - Yusup Kushakov Khaytbaevich (Zien Journals, 2022)
This article discusses the role of teaching a foreign language in modern education and important aspects of learning a foreign language.
Keywords: Foreign language; education; system; democracy